Use of postmenopausal hormone therapy and risk of Alzheimer's disease in Finland: nationwide case-control study - Savolainen-Peltonen H; Rahkola-Soisalo P; Hoti F; Vattulainen P; Gissler M; Ylikorkala O; Mikkola TS (BMJ PUBLISHING GROUP, 2022)
OBJECTIVESTo compare the use of hormone therapy between Finnish postmenopausal women with and without a diagnosis for Alzheimer's disease.DESIGNNationwide case-control study.SETTINGFinnish national population and drug register, between 1999 and 2013.PARTICIPANTSAll postmenopausal women (n= 84 739) in Finland who, between 1999 and 2013, received a diagnosis of Alzheimer's disease from a neurologist or geriatrician, and who were identified from a national drug register. Control women without a diagnosis (n= 84 739), matched by age and hospital district, were traced from the Finnish national population register.INTERVENTIONSData on hormone therapy use were obtained from the Finnish national drug reimbursement register.MAIN OUTCOME MEASURESOdds ratios and 95% confidence intervals for Alzheimer's disease, calculated with conditional logistic regression analysis.RESULTSIn 83 688 (98.8%) women, a diagnosis for Alzheimer's disease was made at the age of 60 years or older, and 47 239 (55.7%) women had been over 80 years of age at diagnosis. Use of systemic hormone therapy was associated with a 9-17% increased risk of Alzheimer's disease. The risk of the disease did not differ significantly between users of estradiol only (odds ratio 1.09, 95% confidence interval 1.05 to 1.14) and those of oestrogen-progestogen (1.17, 1.13 to 1.21). The risk increases in users of oestrogen-progestogen therapy were not related to different progestogens (noreth isterone acetate, medroxyprogesterone acetate, or other progestogens); but in women younger than 60 at hormone therapy initiation, these risk increases were associated with hormone therapy exposure over 10 years. Furthermore, the age at initiation of systemic hormone therapy was not a decisive determinant for the increase in risk of Alzheimer's disease. The exclusive use of vaginal estradiol did not affect the risk of the disease (0.99, 0.96 to 1.01).CONCLUSIONSLong term use of systemic hormone therapy might be accompanied with an overall increased risk of Alzheimer's disease, which is not related to the type of progestogen or the age at initiation of systemic hormone therapy. By contrast, use of vaginal estradiol shows no such risk. Even though the absolute risk increase for Alzheimer's disease is small, our data should be implemented into information for present and future users of hormone therapy.